2020
DOI: 10.1111/xen.12631
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up for the microbiological safety of clinical microencapsulated neonatal porcine islet transplantation

Abstract: Allogeneic islet transplantation has become a viable treatment for unstable type 1 diabetic patients. 1 On the other hand, donor shortage is a serious issue and xenotransplantation, especially using porcine organ, is a promising approach to remedy this situation. 2,3 We have conducted clinical trials of alginate microencapsulated neonatal porcine islets for unstable type 1 diabetic patients in NZ 4,5 and Argentina. 6,7 The alginate microcapsules in which porcine islets were administered are "minimal volume" mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The important strategy is confirming no transfection using co‐culture test with HEK‐293 cells, transplanting the cells with low copy numbers of PERV A and B, following up the recipients and their close relatives for life‐long and archiving samples for long‐term. Recently, we published long‐term PERV infection‐free cases in our islet xenotransplantation patients by complying the regulatory rules 50 . Nevertheless, establishment of a PERV‐free donor could be a useful solution to prevent PERV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The important strategy is confirming no transfection using co‐culture test with HEK‐293 cells, transplanting the cells with low copy numbers of PERV A and B, following up the recipients and their close relatives for life‐long and archiving samples for long‐term. Recently, we published long‐term PERV infection‐free cases in our islet xenotransplantation patients by complying the regulatory rules 50 . Nevertheless, establishment of a PERV‐free donor could be a useful solution to prevent PERV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that other investigators have proposed targeted inactivation of PERV-proviruses present in donor animals [48] a strategy that might be associated with a high risk of genomic rearrangements [56]. However, confidence can be extrapolated from the lack of evidence of PERV and/or pathogen infection, or indeed other adverse events, in human recipients of cellular and skin xenotransplants [57][58][59]. It can be argued that solid organ xenotransplants could be considered a higher risk because of function and site; while no single method can fully eliminate the theoretical risk that PERV presents, a matrix of preventive monitoring and therapeutic measures is a powerful rational basis to now support the clinical application of solid organ xenotransplantation [60,61].…”
Section: Minimizing Infection Riskmentioning
confidence: 99%
“…Patience et al initially described PERV transmission from porcine to human cells in vitro, 60 however, no cases of in vivo transmission of PERV have been documented in preclinical and clinical trials to date 61 . A recent report by Matsumoto et al has shown no presence of PERV (or any other porcine viruses) in patients undergoing encapsulated porcine IXT over a 5‐ to 7‐year follow‐up period 62 ; this coincides with results from the previously mentioned pilot clinical trial by Xiaoqian et al 59 These reports should alleviate any concerns around the microbial safety of porcine IXT, which, coupled with efficient large‐scale isolation of porcine islets should support more clinical trials in the near future.…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%